A STELLAR Role for Knowledge Organization Systems in Digital Archaeology. - Tudhope, Douglas; Binding, Ceri; Jeffrey, Stuart; May, Keith; Vlachidis, Andreas (Bulletin of the American Society for Information Science & Technology)
Research data in archaeology is being made more accessible through the semantic efforts of the STAR and STELLAR projects of two United Kingdom universities. The goal of STAR (Semantic Technologies for Archaeological Resources) is to facilitate semantic interoperability, enabling a structured semantic search of five databases and grey literature reports using an ontology of cultural heritage in combination with other knowledge organization systems. STAR employs natural language processing to identify key concepts and generate semantic metadata to support the unified search. STELLAR (Semantic Technologies Enhancing Links and Linked data for Archaeological Resources) takes the process a step further by simplifying the job of expressing excavation data in CRM ontology terms and then generating representations as linked data. The two projects demonstrate the effectiveness of semantic interoperability methods, coordinating data and vocabularies in a shared framework, and supporting the reuse of archaeological excavation data.